Training Teachers to Conduct Trial-Based Functional Analyses. (November 2013) - Kunnavatana, S. Shanun; Bloom, Sarah E.; Samaha, Andrew L.; Dayton, Elizabeth
The trial-based functional analysis (FA) is a promising approach to identification of behavioral function and is especially suited for use in educational settings. Not all studies on trial-based FA have included teachers as therapists, and those studies that have, included minimal information on teacher training. The purpose of this study was to determine whether teachers trained via an in-service training would be able to conduct trial-based FAs with high procedural integrity. We trained four teachers to conduct trial-based FAs using a combination of didactic teaching and practice with feedback. All four teachers improved performance following training. Performance remained above baseline levels during an in situ maintenance condition, but for three of four teachers, additional feedback was required to recapture performance observed immediately following training.